Lean approach in knowledge work - Hanna Kropsu-Vehkapera; Ville Isoherranen (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: Knowledge work productivity is a key area of improvement for many organisations. Lean approach is a sustainable way to achieve operational excellence and can be applied in many areas. The purpose of this novel study is to examine the potential of using lean approach for improving knowledge work practices. Design/methodology/approach: A systematic literature review has been carried out to study how lean approach is realised in knowledge work. The research is conceptual in nature and draws upon earlier research findings. Findings: This study shows that lean studies' in knowledge work is an emerging research area. This study documents the methods and practices implemented in knowledge work to date, and presents a knowledge work continuum, which is an essential framework for effective lean approach deployment and to frame future research focus in knowledge work productivity. Research limitations/implications: This study structures the concept of knowledge work and outlines a concrete concept derived from earlier literature. The study summarises the literature on lean in knowledge work and highlights, which methods are used. More research is needed to understand how lean can be implemented in complex knowledge work environment and not only on the repetitive knowledge work. The limitations of this research are due to the limited availability of previous research. Practical implications: To analyse the nature of knowledge work, we implicate the areas where lean methods especially apply to improving knowledge work productivity. When applying lean in knowledge work context the focus should be using the people better and improving information flow. Originality/value: This study focuses on adapting lean methods into a knowledge work context and summarises earlier research done in this field. The study discusses the potential to improve knowledge work productivity by implementing lean methods and presents a unique knowledge work continuum to frame previous research and give focus for future research.
Keywords: 650; lean; knowledge work; knowledge work continuum; knowledge work productivity; operational excellence